Wybrane problemy dynamicznej wielowymiarowej analizy porównawczej - Grabiński, Tadeusz (Wydział Prawa i Administracji UAM, 1985)
The work presents assumptions, methods and technics of proceeding elaborated in a multidimensional comparative analysis applied to examine dynamics of economic phenomena. The study is illustrated with the example of analysis of living standard of 22 European states in the years 1960 - 80 on the grounds of 7 diagnostic variables selected from a wider 18-element set of initial variables. Prognoses of synthetic measures of the living standard till 1990 have been constructed, European states are grouped from the viewpoint of a degree and a pace of changes in the living standard. Brackwardness of Poland in relation to other European states in that respect is also estimated.
Selective problems of a dynamic multidimensional comparative analysis